Realignment under Stress: the July 2015 referendum and the September parliamentary election in Greece - Tsatsanis, E. (2017)
The victory of the radical-left SYRIZA in the September 2015 election confounded expectations given the failure of the SYRIZA–ANEL government formed in January either to deliver on its central promise of reversing austerity policies or to capitalise on its major victory in the July referendum. The article examines both the election and the referendum that preceded it, offering an explanation for SYRIZA’s victory. It also attempts to trace the trajectory of the current party system in Greece and its ongoing realignment process in light of the 2015 electoral contests and the busy political timeline since the formation of the first SYRIZA–ANEL government.